Didactics for the teaching-learning processes in the training practice in Hemostasis (Papeles, 2021)
The development of diagnostic tests for the detection of alterations of hemostasis, their interpretation and correlation requires the permanent and detailed study of the biochemical, physiological and pathological processes. The factors that enter to participate in the teaching-learning processes of hemostasis depend on the complexity of the topics, the preconceptions, the applied dynamics, the structuring of the work plan, the methodology and the time required for the apprehension of knowledge. In this work it was applied a range of educational modalities that included special didactics, demonstration activities and experimental learning linked to general didactics. From the literature reviewed and the approach with the resident phisicians through the teaching-service agreement between the Laboratorio de Referencia en Hemostasia with the Universidad Militar Nueva Granada and the Fundación Universitaria de Ciencias de la Salud, it was considered to establish how teaching didactics-learning of hemostasis is articulated in the orientation of praxis for the enhancement of knowledge in a complex area of medicine. A survey of hematology and hematopoietic oncology to resident phisicians was carried out in the period from 2013 to 2016 in order to establish the perception about didactics applied in the specialized rotation of hemostasis, which in 92% were shown to be adequate for the Training of specific skills. Thus, it is proposed the application of didactics that allow the articulation of praxis and complex theory for the empowerment of knowledge and the strengthening, construction and reproduction of learning.
Keywords: medicine; hematology; hematooncology; hemostasis; teaching-learning; didactics